Pregnancy does not affect fecal calprotectin concentration in healthy women - Bálint, Anita; Berényi, Anna; Farkas, Klaudia; Pallagi-Kunstár, Éva; Altorjay, Ábel; Csonka, Andrea; Krizsán, Mária; Szűcs, Mónika; Pál, Attila; Fábián, Anna; Bor, Renáta; Milassin, Ágnes; et al. (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Noninvasive activity markers are extremely important in conditions, such as pregnancy, when endoscopy is not recommended. The aim of this prospective study was to determine fecal calprotectin (FC) concentrations in healthy non-pregnant and pregnant women and in patients with inflammatory bowel disease (IBD). Materials and Methods: Healthy pregnant and non-pregnant women and patients with active and inactive IBD were prospectively enrolled in this study. Demographic and clinical parameters and clinical disease activity scores in patients with IBD were recorded. Blood and stool samples of every patient were obtained to determine C-reactive protein and FC levels. FC levels were measured with a quantitative lateral flow assay. Results: One hundred and thirty-five subjects were enrolled in the study (24 non-pregnant and 48 pregnant healthy women, 40 non-pregnant patients with active IBD and 23 non-pregnant patients with inactive IBD). FC was significantly higher in active IBD patients than in pregnant (p<0.001) and non-pregnant healthy women (p<0.001). No difference could be detected in FC concentrations between pregnant and non-pregnant healthy women. Conclusion: Since FC levels remained unchanged during pregnancy, it may be a useful noninvasive diagnostic tool in pregnancy for monitoring mucosal inflammation.